Deconstructing Minorities in Deliberative Democracy - M Dian Hikmawan (ijd-demos, 2022)
AbstractIt was a project from the inception of democracy to put all people on an equal footing with the rest of society. But in actuality, both in the state and in everyday political practice, segregation between citizens is an unavoidable fact of life that cannot be ignored. This research investigates how the political reality of soundness is viewed within the framework of political theory when it comes to the daily practice of democracy in the context of political theory. This research, which takes a phenomenological perspective, not only explains how the reality of civic politics is in the fight for accessibility and equality of citizens, but it also attempts to comprehend it as a collaborative endeavor to overcome the segregation that exists in everyday civic politics. This study also takes into account cultural discourse in the development of equal citizenship politics.Keywords: minorities, deliberative, recognition, democracy AbstrakIde dalam menempatkan warga negara kedalam posisi yang setara merupakan projek sedari awal dari demokrasi. Namun pada praktiknya dalam bernegara dan praktik politik keseharian segregasi antar warga menjadi realitas yang tidak dapt di hindari. Riset ini menulusur bagai mana realitas politik kesehatian dalam kerangka teori politik dalam melihat praktik demokrasi keseharian. Dengan pendekatan phenomelogy, penelitian ini tidak hanya menjelaskan bagaimana realitas politik kewargaan dalam memperjuangkan aksesibilitas dan kesetaraan warga namun lebih jauh mencoba memahaminya sebagai upaya Bersama dalam menanggulangi segregasi yang ada dalam politik kewargaan sehari-hari. Penelitian ini juga menawarga diskursus kultural dalam membangun politik kewargaan yang setara.Kata Kunci: minoritas, deliberative, rekognisi, demokrasi